Erwerbungen : 80/81. - Städtisches Kunstmuseum Bonn (Bonn : Städtisches Kunstmuseum Bonn, 1982)
Macke, August ; Beuys, Joseph ; Nauen, Heinrich ; Nauen von Malachowski, Clara Maria ; Dienz, Herm ; Baumgarten, Lothar ; Darboven, Hanne ; Droese, Felix ; Fiebig, Eberhard ; Gerz, Jochen ; Gosewitz, Ludwig ; Graubner, Gotthard ; Hafner, Jonas ; etc.
Erwerbungen : 80/81, Städtisches Kunstmuseum Bonn, 8.7.-29.8.1982
boek